Microstructure and mechanical properties of WB2–B4C composites fabricated by boro/carbothermal reduction and SPS. Issue 4 (26th December 2022) - Long, Ying; Zhang, Guihao; Lin, Shiming; Lin, Hua‐Tay
Abstract: The phase composition, microstructure, and mechanical properties of the WB2 –B4 C composites fabricated by a combination of boro/carbothermal reduction and spark plasma sintering (SPS) method with WO3, B4 C, and graphite as raw materials were investigated in this study. The experimental results showed that the relative density of the as‐sintered WB2 –B4 C composites was ∼93.1% and ∼99.5%, respectively, after being SPS sintered at 1600°C under the applied load of 30 MPa for 10 min. Scanning electron microscope analysis showed that a network structure with WB2 grains surrounded by B4 C grains was observed after sintering. Analyses of high‐resolution TEM showed semi‐coherent interface and lattice distortion transition region between WB2 and B4 C grains. The Vickers hardness of WB2 –B4 C composite increased to 22.3 ± 0.9 GPa at 9.8 N owing to the fully dense, solid solution of C, and three‐dimensional network structure. Moreover, the fracture toughness and flexural strength of WB2 –B4 C composite reach 6.04 ± 0.81 MPa m 1/2 and 750 ± 80 MPa, respectively, which could be attributed to the semi‐coherent interface between WB2 and B4 C grains.